2017
DOI: 10.1002/jcc.24752
|View full text |Cite
|
Sign up to set email alerts
|

Metallic monoboronyl compounds: Prediction of their structure and comparison with the cyanide analogues

Abstract: A theoretical study of monoboronyls of different metals has been carried out. We have chosen Mg as representative of s-block elements, Al for the p-block, and Group 11 metals (Cu, Ag, and Au) for the d-block. Different behaviors are observed: bonding through the oxygen atom is preferred in the case of Al, for all Group 11 monoboronyls bonding through the boron atom prevails and both interactions give rise to almost isoenergetic compounds in the case of Mg. Predictions for the spectroscopic parameters relevant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 81 publications
3
10
0
Order By: Relevance
“…70 The low values of the electronic charge density, ρ(r), and positive values of its Laplacian, ∇ 2 ρ(r), are indicative of a closed-shell interaction, whereas the negative value of the total energy density, H(r), suggests a certain character of covalent interaction. Therefore, as in previous studies, 29,70 the B−O bonds in the present case of second-row monoboronyls can be classified as mixed covalent/ionic interactions. As pointed out in a previous study, 29 this behavior is in contrast with that observed for the C−N bonds in cyanide/isocyanide compounds, which exhibits clear characteristics of mainly shared (covalent) interaction: high values of ρ(r), negative values of ∇ 2 ρ(r), negative values of H(r), and also relationships between the potential energy density and the kinetic energy density, V(r)/G(r), greater than 2.…”
Section: Resultssupporting
confidence: 69%
See 3 more Smart Citations
“…70 The low values of the electronic charge density, ρ(r), and positive values of its Laplacian, ∇ 2 ρ(r), are indicative of a closed-shell interaction, whereas the negative value of the total energy density, H(r), suggests a certain character of covalent interaction. Therefore, as in previous studies, 29,70 the B−O bonds in the present case of second-row monoboronyls can be classified as mixed covalent/ionic interactions. As pointed out in a previous study, 29 this behavior is in contrast with that observed for the C−N bonds in cyanide/isocyanide compounds, which exhibits clear characteristics of mainly shared (covalent) interaction: high values of ρ(r), negative values of ∇ 2 ρ(r), negative values of H(r), and also relationships between the potential energy density and the kinetic energy density, V(r)/G(r), greater than 2.…”
Section: Resultssupporting
confidence: 69%
“…Therefore, as in previous studies, 29,70 the B−O bonds in the present case of second-row monoboronyls can be classified as mixed covalent/ionic interactions. As pointed out in a previous study, 29 this behavior is in contrast with that observed for the C−N bonds in cyanide/isocyanide compounds, which exhibits clear characteristics of mainly shared (covalent) interaction: high values of ρ(r), negative values of ∇ 2 ρ(r), negative values of H(r), and also relationships between the potential energy density and the kinetic energy density, V(r)/G(r), greater than 2. Thus, although isoelectronic, CN and BO species show important differences in nature.…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…The chemical reactivities of the BO radical with organic molecules have also been investigated in crossed molecular beam experiments under single collision conditions. The first boronyl metal complex to be synthesized in the bulk involved a BO ligand coordinated to a Pt atom, which was also protected by other bulky ligands . This landmark work has stimulated significant further interests in boronyl chemistry. …”
Section: Introductionmentioning
confidence: 99%